The Influence of Human Rights on Death Penalty Sentences in Abolitionist versus Retentionist Perspectives - Joko Cahyono (Journal of Social Science, 2024)
The influence of Human Rights on the death penalty provides a wide space for pro and contra ideologies, therefore the provisions of the death penalty in Indonesia also need to be updated to adjust to these developments, especially in adjusting the moral and cultural values adopted by the Indonesian people. This study aims to determine the policy of formulating the death penalty in Indonesian criminal legislation today, and to analyze the ideal legal formulation policy that is aspired to. This study produces the fact that the law in Indonesia currently does not regulate the death penalty that provides a sense of acceptance by the community, so that there is still conflict between groups who want to abolish the death penalty and groups who want to continue to apply the death penalty. The death penalty is needed as an evaluative process for prisoners in serving their sentences and respect for human rights in accordance with national and international insights.